The Investment Performance of U.S. Equity Pension Fund Managers: An Empirical Investigation - Coggin, T. Daniel; Fabozzi, Frank J.; Rahman, Shafiqur (Journal of Finance, 1993)
This paper presents an empirical investigation of the security selection and market timing performance of a random sample of 71 U.S. equity pension fund managers using monthly returns for the period 1983-1990.The 71 equity fund managers include banks, insurance companies and investment advisors who have been allocated funds by pension plan sponsors.The data were provided by the Frank Russell Company of Tacoma, WA.While there have been many studies of U.S. equity mutual funds, ours is the first such study of which we are aware of U.S. equity pension fund managers.The estimates of selectivity and timing were derived using the Treynor and Mazuy (1966) model and the Bhattacharya and Pfleiderer (1983) model.The total sample of managers is subdivided into four groups by investment style, and a benchmark portfolio is identified for each style.We also included two benchmarks for the broad equity market.Regardless of the choice of a benchmark portfolio or estimation model, the selectivity measure is positive on average and the timing measure is negative on average.However, both selectivity and timing do appear to be somewhat more sensitive to the choice of a benchmark portfolio (and, possibly, the time period) when managers are classified by investment style.A metaanalysis was performed to quantify the effect of sampling error on the cumulated regression results.In every case, meta-analysis revealed some real variation (in excess of that attributable to sampling error) around the mean values for both selectivity and timing.An examination of the 80% probability intervals for selectivity revealed that the best managers can deliver substantial risk-adjusted excess returns.Finally, consistent with previous studies of equity mutual fund performance, we also found a negative correlation between selectivity and timing.However, we argue that the observed negative correlation in our data is largely an artifact of negatively correlated sampling errors for the two estimates.The Investment Performance of U.S. Equit>' Pension Fund Managers: An Empirical InvestigationEach year Pensions & Investments , a leading trade newspaper for the pension management industry, profiles the top 1000 pubUc and private U.S. pension funds.At year-«Kl 1990, these funds had total pension assets of $1,876 trillion.Approximately $750 billion (40 percent) was invested in equities.The Investment Company Institute estimates that $250 billion was invested in open-and closed-end equity-oriented U.S. mutual funds at year-end 1990.This snapshot indicates a 3:1 ratio for p«ision fund equity investment versus mutual fund equity investment.Not only is the dollar difference large, but also the difference in the number of managers in each universe is large.The total number of pension fund managers is much larger than the number of mutual fund managers, by a ratio of approximately 10:1.Yet surprisingly little research has been done on the investment performance of U.S. equity pension fund managers.This paper begins to fill an important gap in the literature by providing empirical evidence on the investment performance of these managers.The focus of this study is on equity pension fund managers who have been allocated funds by a pension plan sponsor.Brinson, Hood and Beebower (1986), Ippolito and Turner (1987), and Berkov-tiz, Finney and Logue (1988) examined the investment performance of a sample of large U.S. pension plans.Each plan may be composed of many fund managen in different asset categories with their own specific investment objectives and styles.In a recent study containing a wealth of informatioQ about the pension management industry, Lakonishok, Shleifer and Vishny (1992) examined the annual returns of a sample of equity pension funds over